The role of POs and LGU in addressing Tiempos Muertos in three haciendas in La Castillana, Negros Occidental. - Goco, Natasha Kim Naig
The research had the following objectives: 1) to identify the programs and policies of the LGU in addressing the scarcity of food and unemployment during the Tiempos Muertos in La Castellana, Negros Occidental; 2) to identify the material and human resource s allocated by POs and the LGU for the said programs and policies; 3) to assess the effectiveness of the measures initiated by the Local Government and POs in addressing the problem of the sugarcane workers in La Castellana during the Tiempos Muertos and; 4) to determine the lessons learned from measures to address the problem, Respondents were selected from three haciendas covered in the study., Results showed that sugarcane workers in three haciendas both utilize individual and group efforts in addressing the problem during the Tiempos Muertos, with group efforts more adequate addressing the problem. Adequate resources in initiating measures had been found very essential in teh determination of the effectivity of the measures. POs received support from non-governmental organizations, government agencies and private individuals and institutions Diversification of crops and provision of livelihood projects were seen to address the problem more. The research recommended that a more quantitative research could further enhance the results of the study.